Energy efficient spectrum resources usage in WPANs : IEEE 802.15.4 MAC sub-layer protocols - Velez, Fernando J.; Borges, Luís Miguel; Barroca, Norberto (Research assistant); Chatzimisios, Periklis (River Publishers series in communications and networking, 2023)
"This research reveals the importance of an appropriate design for the MAC sub-layer protocol for the desired WSN application. Depending on the mission of the WSN application, different protocols are required. Therefore, the overall performance of a WSN application certainly depends on the development and application of suitable e.g., MAC"-- Provided by publisher.